Effects of Aerodynamic Flutter on a Flight Surface Actuator - Gadsden S (My University, 2007)
The purpose of this paper was to study the effects of aerodynamic flutter on a flight surface actuator. The forces generated by this type of flutter were studied on an electrohydrostatic actuator (EHA). The effects of flutter were modeled and analyzed. Current methods of controlling flutter include dynamic mass loading and changing stiffness by design. The paper proposed an alternative way to dynamically control the effects of flutter on flight surfaces that use electrohydrostatic actuation. Through analysis, it was found that in EHA systems, two parameters would impact the response of flutter: damping (B) of the mechanical load, and the effective bulk modulus of the hydraulic oil (βe). There are systems available that can be implemented to change these variables dynamically. The results of changing these variables are discussed and presented here.